Por um Do in antropológico " - Pontos de Cultura e paradigmas nas políticas públicas culturais - Nunes, Ariel Ferreira (2012)
The public cultural policies traditionally increased the high culture and folklore as the main manifestations of Brazilian culture. Since the management of the Minister Gilberto Gil (2003- 2008) we situate changes in the ways of making public policy culture. The main action of this management policy is the implementation of “Cultura Viva” and the “Pontos de Cultura”, operating through the shared management between federal government and civil society. In this work we analyze the implementation of public cultural policy, as well as their modes of organization in social networks and virtual. The ethnography constitutes an open-ended interviews and participant observation in the “Pontos de Cultura”, in their virtual network, and the meetings between “Pontos de Cultura”, local politicians and representatives of the Ministry of Culture, called Teias. Fieldwork focused on the coordinators of the “Pontos de Cultura”, known as ponteiros. These ponteiros are included here as the main organizers of “Pontos de Cultura”, government and society.